Use of digital channels in higher education - Viveros Almeida, Luis Homero; Miranda Realpe, Jorge Humberto; Yandún Velastegui, Marco Antonio (Tierra Infinita, 2022)
The purpose of this study was to characterize the use of digital media in the academic context of students and teachers, considering the problems derived from the applications of digital channels in daily life and at the level of university studies, for this purpose we worked from the paradigm of social constructivism. A quantitative approach of descriptive and cross sectional type was applied, applying a questionnaire to students and professors of the Universidad Politécnica Estatal del Carchi of the different careers of engineering and social sciences. The main results allow us to understand that the main access equipment to digital media is the cell phone and secondly the personal computer, the use of social networks is preferred, but the use of channels for academic purposes is also accepted in a majority way, generating connections up to four times per day for such use, regardless of the role of the researched, whether it is a teacher or student and regardless of gender, since the same response trends are observed in any of the cases.